Diagnosis of management of bacterial wilt and late blight in potato in Ethiopia: A systems thinking perspective - Damtew, Elias; Tafesse, S.; Lie, R.; Mierlo, B. van; Lemaga, B.; Sharma, K.; Struik, P.C.; Leeuwis, Cees (Informa UK Limited, 2018)
Potato is one of the most important food crops for smallholder farmers in the Ethiopian highlands. Diseases, particularly bacterial wilt (caused by Ralstonia solanacearum) and late blight (caused by Phytophthora infestans), are among the major constraints of potato production, despite continuous efforts to control them. Bacterial wilt and late blight are complex problems with multiple technical and institutional features, involving multiple actors with different perceptions and understanding, not only of the problem but also of possible solutions. Appreciating such complexity, this study adopted a systems thinking perspective. It aimed to explore actors’ understanding of the complex problem situation and its implication for the management of the diseases at a collective level. Using a multi-stakeholder workshop and in-depth interviews, a qualitative study was conducted with actors that are directly or indirectly involved in the management of the two diseases. Results showed that actors essentially overlooked key systemic problems in the management of the two diseases. This is mainly reflected in actors’ tendency to give event-level responses, shift responsibilities and engage in a mutual blaming to the problem of bacterial wilt and late blight. Lack of a preventive disease management culture, limited recognition of interdependencies among activities of actors, power inequalities, and top-down and linear approaches in information and knowledge sharing are identified as key structural problems that are underrated by the actors. We contend that the most appropriate way forward towards the management of both diseases is designing and implementing management strategies that, on the one hand, are preventive of disease epidemics, and, on the other hand, foster horizontal information sharing, learning and collective action among the local actors in the system. Digital platforms, particularly mobile-based technologies, can play a role in catalyzing new forms of information sharing, broader learning, and collaboration among farmers and local actors.